Stop Turning a Blind Eye: Tobacco Smoking Among Egyptian Patients With Schizophrenia - Elkholy, Hussien; Nagy, Nahla; Taha, Ghada R. A.; Elhabiby, Mahmoud; Yosef, Mostafa; Azzam, Lobna (Frontiers in Psychiatry, 2019)
Background Patients with schizophrenia have considerably higher rates of mortality than general population. Multiple factors may play a role in this. Despite being a major preventable cause of death in general population, smoking is usually overlooked when dealing with patients with schizophrenia. Understanding the pattern of smoking, its severity and the reasons to quit might be helpful in managing patients with schizophrenia and decreasing the mortality gap. Subjects and Methods The study included smokers divided into two groups; the first included 346 patients with schizophrenia while the second group had 150 smokers with no mental illness. Both groups were assessed and compared regarding sociodemographic variables, pattern of smoking, severity of nicotine dependence and motivation to quit smoking. Results Earlier age of starting to smoke, higher number of cigarettes per day and lower dependency scores were noted in patients with Schizophrenia. Positive correlation was found between positive symptoms and severity of dependence. Specific positive symptoms were correlated to number of cigarettes per day, time before first cigarette. Patients with Schizophrenia showed a significant difference in intrinsic reasons to quit (health concerns and self-control), which were also positively correlated to their positive symptoms score. Linear regression analysis for predictors of FTND score, it was revealed that only age, sex and schizophrenia were significant predictors of FTND score. Conclusion Patients with schizophrenia smoke at earlier ages and smoke more cigarettes per day, yet, have less severe dependence than non-schizophrenic counterparts. Positive symptoms play a role in their smoking pattern and severity. Health concerns and self-control are their main motives to quit smoking.